AFLATOXINS IN FOOD GRAINS: CONTAMINATION, DANGERS AND CONTROL - Abdullahi, N.; Dandago, M. A. (FUDMA JOURNAL OF SCIENCES, 2022)
The most concern postharvest safety issue in food grains is aflatoxins production in contaminated stored grains. Consumption of aflatoxins contaminated grains can lead to complicated health issues that can lead to death. Aflatoxins are secondary metabolites commonly produced by Aspergillus flavus and Aspergillus parasiticus. They were reported to disturb foetus development, causes changes in living cells, suppresses the immune system and causes many forms of cancers. Aflatoxin B1 was classified under group I carcinogens by the International Agency for Research on Cancer. Aflatoxins contamination affects food security and can hinder international trade due to the strict ban enforce by many nations. Contaminations were reported in raw and processed grains (including ready-to-eat), milk and meat of farm animals and human breastmilk and blood. Major causes of grains aflatoxins contamination are wrong harvesting time and method, improper drying, poor storage and processing and higher moisture in the grains. Literature was gathered through an online search on Google Scholar, attention was given to the articles published in the last 5 years. Causes of fungal contamination, aflatoxins production and their control measures were deliberated, possible means of mitigating aflatoxins contamination through consumption of food grains were also recommended
Keywords: mycotoxins, storage, drying, cereals, legumes